Superluminous supernova progenitors have a half-solar metallicity threshold. Issue 3 (9th June 2017) - Chen, Ting-Wan; Smartt, Stephen J.; Yates, Rob M.; Nicholl, Matt; Krühler, Thomas; Schady, Patricia; Dennefeld, Michel; Inserra, Cosimo
Abstract: Host galaxy properties provide strong constraints on the stellar progenitors of superluminous supernovae. By comparing a sample of 19 low-redshift ( z < 0.3) superluminous supernova hosts to galaxy populations in the local Universe, we show that sub-solar metallicities seem to be a requirement. All superluminous supernovae in hosts with high measured gas-phase metallicities are found to explode at large galactocentric radii, indicating that the metallicity at the explosion site is likely lower than the integrated host value. We found that superluminous supernova hosts do not always have star formation rates higher than typical star-forming galaxies of the same mass. However, we confirm that high absolute specific star formation rates are a feature of superluminous supernova host galaxies, but interpret this as simply a consequence of the anticorrelation between gas-phase metallicity and specific star formation rate and the requirement of on-going star formation to produce young, massive stars greater than ∼10–20 M⊙ . Based on our sample, we propose an upper limit of ${\sim } 0.5\, \, \rm {Z}_{\rm {\odot }}$ for forming superluminous supernova progenitors (assuming an N2 metallicity diagnostic and a solar oxygen abundance of 8.69). Finally, we show that if magnetar powering is the source of the extreme luminosity, then the required initial spins appear to be correlated with metallicity of the host galaxy. This correlation needs further work, but if it applies, it is a powerful link between the supernova parameters and nature of the progenitor population.